Formação continuada pela aprendizagem baseada em projetos: atuação no desenvolvimento profissional docente de professores formadores - Câmara, Aldemira de Araújo (2021)
This research had the purpose to understand in which aspects a Continuing Education, based on Project-Based Learning, can act in the Teacher Professional Development of trainer teachers, since it is a consensus that the demand for good results in student learning increasingly requires trained and qualified teachers; this concerns, which should not only be during their initial training, but throughout their professional life and continuing education. There are three basic concepts in the research: Continuing Education, Teacher Professional Development (DPD) and Project-Based Learning (PBL). The research was carried out at the Educational Technology Management (GTE) of the Municipal Education Department of Manaus, with 08 (eight) trainers teachers who work in the coordination of training projects that GTE implements with teachers from the municipal education network. Action research was used, from Tripp (2005), to understand and improve the research process, through a cycle of 3 (three) phases: planning, implementation and evaluation. The process experienced throughout these phases allowed the organization of the educational product of this research, namely: "Proposal for the elaboration of training projects by the PBL for the teacher professional development of trainers teachers", with the objective of contributing to the Teacher Professional Development (DPD) of trainers teachers through the development of training projects based on Project-Based Learning (PBL). From the perspective of the Data Analysis Spiral (CRESWELL, 2014), the data was analyzed to understand and respond to the research problem, as being qualitative research, it is concerned with understanding the phenomenon, its senses and meanings that the build (MORAES; GALIAZZI, 2016). The results of the research induced that Continuing Education, based on Project-Based Learning, acted in the Teacher Professional Development of trainer teachers in 03 (three) aspects: 1) recognition of the importance of reflecting on their own practice to generate changes; 2) recognition of the school context as a formative and potentiating element of professional practices; and 3) recognition of the importance of acting in the management of their own training processes for the development of professional skills.